Delivering Beneficial Microorganisms for Corals: Rotifers as Carriers of Probiotic Bacteria - Assis, Juliana M.; Abreu, Fernanda; Villela, Helena M. D.; Barno, Adam; Valle, Rafael F.; Vieira, Rayssa; Taveira, Igor; Duarte, Gustavo; Bourne, David G.; Høj, Lone; Peixoto, Raquel S. (Frontiers in Microbiology, 2020)
The use of Beneficial Microorganisms for Corals (BMCs) to increase the resistance of corals to environmental stress has proven to be effective in laboratory trials. Because direct inoculation of BMCs in larger tanks or in the field can be challenging, a delivery mechanism is needed for efficient transmission of the BMC consortium. Packaged delivery mechanisms have been successfully used to transmit probiotics to other organisms, including humans, lobsters, and fish. Here, we tested a method for utilizing rotifers of the species Brachionus plicatilis for delivery of BMCs to corals of the species Pocillopora damicornis. Epifluorescence microscopy combined with a live/dead cell staining assay was used to evaluate the viability of the BMCs and monitor their in vivo uptake by the rotifers. The rotifers efficiently ingested BMCs, which accumulated in the digestive system and on the body surface after 10 minutes of interaction. Scanning electron microscopy confirmed the adherence of BMCs to the rotifer surfaces. BMC-enriched rotifers were actively ingested by P. damicornis corals, indicating that this is a promising technique for administering coral probiotics in situ. Studies to track the delivery of probiotics through carriers such as B. plicatilis, and the provision or establishment of beneficial traits in corals are the next proof-of-concept research priorities.